Analisis Harga Pokok Produksi pada Usaha Dagang - Ayu Dwi Nursida; Arik Susbiyani; Ibna Kamelia Fiel Afroh (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The Full costing method is a method of determining the cost of goods manufactured which calculates all cost elements that have variable or fixed behavior. The purpose of this study is as follows: (1) to determine the calculation of the cost of production at UD. Yanki im Banyuwangi . (2) to apply the calculation of the cost of production based on the price method full costing at UD. Yanki im Banyuwangi. (3) to compare and analyze the results of the calculation of cost of goods manufactured by UD. Yanki im Banyuwangi by calculating the cost of production according to the researcher. In this study the method used to determine the cost of production is the full costing method, because the full costing method takes into account all elements of production costs (main raw material costs, direct labor costs, and factory overhead costs) into the cost of production. The informants in this study were the owners and production parts of Company .Data collection techniques used in this study were participatory observation, in-depth interviews,and documentation. Based on the calculation of the cost of production after being in accordance with the concept of cost accounting, there is a difference in the calculation of the cost of production between the company and the author.The cost of production for 2x3m drawers, 2x2m beds, 2.5x2.5m doors,4x4m frames and 4x4m cabinets,according to the author, is smaller than the company's calculations. This is because the company overestimates overhead costs. This greatly affects the determination of the selling price. Keywords: cost of production,Manufactured, Full costing